Tidal rhythmites of the Marais Vernier Seine estuary, France and their implications for relative sea-level - Frouin, Millena; Sebag, David; Laignel, Benoit; Ogier, Sylvie; Verrecchia, Eric; Durand, Alain (My University, 2006)
The Marais Vernier, located in the upper reaches of the Seine River Estuary (northern France), preserves a thick Holocene succession of laminated detrital deposits and peats. The spectral analysis of one laminated deposit suggests that tidal processes were largely responsible for supplying sediments to this system. Two periods (16 and 32 laminae per cycle) were identified. These cycles can be related to either both the synodic neap–spring cycle (the so-called “fortnightly cycle”) and the anomalistic monthly cycle or both the semiannual and annual tidal cycles. The recognition of tidal influence on these deposits provides insight into the likelihood of some relative sea-level fluctuations previously inferred from these sediments. The depositional rates calculated for the laminated deposits, based on the recognition of these tidal cycles, suggest that the time interval required to deposit the sediments was far shorter than is implied by considering rates based on regional sea-level rise alone.
Keywords: tidal rhythmites; spectral analysis; wetlands; Holocene; Seine estuary